Analysis for Technology Acceptance of Internal Apps at Regency Level in Indonesia - Ines (PT. Lentera Ilmu Publisher, 2024)
This study investigates the factors influencing technology acceptance of internal applications within regency-level government institutions in Indonesia, utilizing the Technology Acceptance Model (TAM). The analysis focuses on key variables including perceived usefulness (PU), perceived ease of use (PEOU), attitude toward using (ATU), behavioural intention to use (BITU), and actual system usage (ASU). The results reveal strong correlations across all variables, indicating a high level of acceptance and positive engagement with the apps among government employees. Additionally, reliability testing shows high internal consistency, with Cronbach's Alpha values exceeding 0.9 for most variables, confirming the stability and dependability of the measurements. These findings suggest that government employees generally find the internal apps beneficial and user-friendly, leading to favorable attitudes and continued usage. This research provides valuable insights that can inform the development and implementation of future digital initiatives at the regency level in Indonesia.